Parenting styles and self-regulation in shaping elementary students’ learning independence - Siti Masyithoh; Ahmed Ali Loukam; Asep Ediana Latip; Rika Sa’diyah; Syifa Musyarrofah (Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning independence is an important character trait in primary education that supports independent and lifelong learning abilities. Although parental upbringing and self-regulation have been extensively studied by academics, their relative contributions in the context of collectivist cultures are still not fully understood. This study aims to analyse the relationship between parental parenting styles and self-regulation in shaping the learning independence of elementary school students. This research uses a quantitative approach with a causal-comparative design. Data was obtained from 58 fifth-grade students in Sawangan District, Depok City, and analysed using two-way ANOVA (3x2). The research results indicate that parenting style contributes 4.4% to students' learning independence, while self-regulation contributes 50.3%. These findings indicate that students' internal capacity, particularly self-regulation skills encompassing metacognitive, motivational, and behavioural aspects, has a more dominant influence than external factors such as parental parenting styles. Parenting styles did not show a significant direct influence, and no significant interaction was found between parenting styles and self-regulation. This finding confirms that students' internal ability to regulate their learning process plays a more decisive role than external factors. In the context of a collectivistic culture, parenting serves as a supportive framework for the development of self-regulation and learning independence.